2019
DOI: 10.1016/j.jenvman.2018.11.065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of barium on the pathways of anaerobic digestion

Abstract: The sufficient presence of trace elements (TE) is essential for anaerobic digestion. Barium (Ba) is considered a non-essential trace element that can be collaterally added to digesters as part of low-cost trace element sources or because of its presence in some feedstocks, such as crude glycerol. In the present study, the impact of Ba supplementation (2-2,000 mg/L) on each stage of the anaerobic digestion (AD) process was evaluated using pure substrates (i.e., cellulose, glucose, a mixture of volatile fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Wyman et al 44 . indicated that the role of trace elements in the AD was associated with their function as co‐factors of different enzymes involved throughout the anaerobic pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wyman et al 44 . indicated that the role of trace elements in the AD was associated with their function as co‐factors of different enzymes involved throughout the anaerobic pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Wyman et al 44 indicated that the role of trace elements in the AD was associated with their function as co-factors of different enzymes involved throughout the anaerobic pathway. Nevertheless, if these concentrations are too high, there is an inhibition of the process that can be attributed to an alteration of the function and structure of enzymes by joining metal ions with thiol groups in protein molecules 26,45 This demonstrates that the supplementation of trace elements in anaerobic digesters should be considered on a case-by-case basis.…”
Section: Fly Ash (Fa) As Micronutrient Sourcementioning
confidence: 99%
“…Therefore each case of anaerobic digestion should be pretested, to determine the feasibility of adding the crude glycerol. Factors such as pH, temperature, redox potential, organic loading rate (OLR), hydraulic retention time (HRT), macronutrients, micronutrients, trace elements (TE), volatile fatty acids (VFA), ammonia, and electrical conductivity (EC) play an important role in the growth and activity of microorganisms (Roussel et al, 2019;Wyman et al, 2019). Recent studies have shown that microelements such as iron (Fe), zinc (Zn), chromium (Cr), copper (Cu), magnesium (Mg), nickel (Ni), manganese (Mn), barium (Ba), and others play an important role in the biogas production process (Schattauer et al, 2011;Wyman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as pH, temperature, redox potential, organic loading rate (OLR), hydraulic retention time (HRT), macronutrients, micronutrients, trace elements (TE), volatile fatty acids (VFA), ammonia, and electrical conductivity (EC) play an important role in the growth and activity of microorganisms (Roussel et al, 2019;Wyman et al, 2019). Recent studies have shown that microelements such as iron (Fe), zinc (Zn), chromium (Cr), copper (Cu), magnesium (Mg), nickel (Ni), manganese (Mn), barium (Ba), and others play an important role in the biogas production process (Schattauer et al, 2011;Wyman et al, 2019). Sufficient concentrations and bioavailability of various TEs can lead to stable and more efficient methane production, while a deficiency or overload can lead to imbalances or complete failure of the process (Wintsche et al, 2016;Wyman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation